Development Digitization In Enhancement Potency Tour Village Through Smart Village Concept in the Village Permis and Rajik South Bangka Regency - Julia Julia; Rahil Imainul Aprilian; Yanto Yanto (Future Science, 2022)
Tourism is a sector that has the potential to be developed as a source of regional income, because in addition to providing benefits for the tourist attractions themselves, it also provides benefits to the supporting infrastructure, such as restaurants, lodging places, industrial centers, souvenir centers, etc. Digitization of tourism is one of the important strategies in responding to the digital-oriented civilization of society in meeting their needs for traveling. Digitization of tourism is considered the right step in promoting tourism through a digital approach that has an impact on the development of tourism potential in a tourist village. Based on the results of field observations, various problems were found in Permis and Rajik Villages, South Bangka Regency, namely the lack of efforts to publicize tourism potential in Permis and Rajik villages. Lack of knowledge of the village government regarding website creation.